2020
DOI: 10.3389/fmicb.2020.01803
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine Arrests Growth of the Model Diatom Phaeodactylum tricornutum by Increasing Oxidative Stress and Altering Energetic and Lipid Metabolism

Abstract: Antidepressant Induces Metabolic Stress in Diatoms biomarkers. Additionally, the negative impact of this pharmaceutical molecule on the primary productivity is also evident alongside with an increase in respiratory oxygen consumption. From the ecological point of view, reduction in diatom biomass due to continued exposure to fluoxetine may severely impact estuarine and coastal trophic webs, by both a reduction in oxygen primary productivity and reduced availability of key fatty acids to the dependent heterotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 98 publications
(160 reference statements)
4
67
0
Order By: Relevance
“…The presence of this antidepressant in plants can therefore have implications in the aquatic life. This was previously reported for the marine diatom Phaeodactylum tricornutum [9], showing that this compound severy impaired the photochemical metabolism and biomass production of this autotrophic specie. For example, Ford et al [34] reported that they found significant effects on foot detachment in snail species and righting times at the high (1 mg L −1 ) concentration of FLU, however, this concentration is higher than might be expected from wastewater treatment plants.…”
Section: Influence Of Xenobiotics On Biomass Yieldsupporting
confidence: 80%
See 1 more Smart Citation
“…The presence of this antidepressant in plants can therefore have implications in the aquatic life. This was previously reported for the marine diatom Phaeodactylum tricornutum [9], showing that this compound severy impaired the photochemical metabolism and biomass production of this autotrophic specie. For example, Ford et al [34] reported that they found significant effects on foot detachment in snail species and righting times at the high (1 mg L −1 ) concentration of FLU, however, this concentration is higher than might be expected from wastewater treatment plants.…”
Section: Influence Of Xenobiotics On Biomass Yieldsupporting
confidence: 80%
“…These contaminants include pharmaceuticals, pesticides, steroid hormones, personal care products, industrial and household products, metal nanoparticles, surfactants, industrial additives, paints, flame retardants and solvents. Many of these compounds are used and released into the environment, leading to acute and chronic toxicity events, metabolic and endocrine disruption in humans and aquatic wildlife [5][6][7], and the development of bacterial pathogen resistance, impairment of marine primary productivity [8][9][10][11], among other effects [12]. Mainly due to microbial resistance, antibiotics found in different sources have attracted the attention of the scientific community.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical significance was considered at p < 0.05. A multivariate approach was employed to test for variations in the complete photochemical and fatty acid metabolism [ 37 , 56 , 57 ]. Canonical analysis of principle (CAP) coordinates, using Euclidean distances, were preformed to plot in a canonical space the dissimilarities regarding fatty acids and photochemical studied variables while preforming a cross-validation step and determining the allocation efficiency into the different treatment groups.…”
Section: Methodsmentioning
confidence: 99%
“…Any disturbance at this level has inevitable impacts on the whole marine ecosystem. Contaminants toxic effects are known to have severe and specific influence on these organisms, especially impairing their photosynthetic metabolism [ 6 , 7 , 8 , 9 , 10 ]. Having both biochemical and biophysical components allows the photosynthetic mechanisms to be addressed remotely [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Any disturbance at this level has inevitable impacts on the whole marine ecosystem. Contaminants toxic effects are known to have severe and specific influence on these organisms, especially impairing their photosynthetic metabolism [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%